Vastarena, a new genus for the New Caledonian cicada Abroma pumila Distant (Insecta: Hemiptera, Cicadoidea, Cicadidae) - Delorme, Quentin (Zootaxa, 2016)
In New Caledonia, the species Abroma pumila (Distant, 1892) shows several incompatibilities with the genus type species A. guerinii (Signoret, 1860). A new genus, Vastarena, is proposed.